Dipeptidyl peptidase IV deficiency increases susceptibility to angiotensin-converting enzyme inhibitor–induced peritracheal edema - Byrd, James Brian; Shreevatsa, Ajai; Putlur, Pradeep; Foretia, Denis; McAlexander, Laurie; Sinha, Tuhin; Does, Mark D.; Brown, Nancy J. (Journal of allergy and clinical immunology, 2007)
Serum dipeptidyl peptidase IV (DPPIV) activity is decreased in some individuals with ACE inhibitor–associated angioedema. ACE and DPPIV degrade substance P, an edema-forming peptide. The contribution of impaired degradation of substance P by DPPIV to the pathogenesis of ACE inhibitor–associated angioedema is unknown. We sought to determine whether DPPIV deficiency results in increased edema formation during ACE inhibition. We also sought to develop an animal model using magnetic resonance imaging to quantify ACE inhibitor–induced edema. The effect of genetic DPPIV deficiency on peritracheal edema was assessed in F344 rats after treatment with saline, captopril (2.5 mg/kg), or captopril plus the neurokinin receptor antagonist spantide (100 μg/kg) by using serial T2-weighted magnetic resonance imaging. Serum dipeptidyl peptidase activity was dramatically decreased in DPPIV-deficient rats ( P < .001). The volume of peritracheal edema was significantly greater in captopril-treated DPPIV-deficient rats than in saline-treated DPPIV-deficient rats ( P = .001), saline-treated rats of the normal substrain ( P < .001), or captopril-treated rats of the normal substrain ( P = .001). Cotreatment with spantide attenuated peritracheal edema in captopril-treated DPPIV-deficient rats ( P = .005 vs captopril-treated DPPIV-deficient rats and P = .57 vs saline-treated DPPIV-deficient rats). DPPIV deficiency predisposes to peritracheal edema formation when ACE is inhibited through a neurokinin receptor–dependent mechanism. Magnetic resonance imaging is useful for modeling ACE inhibitor–associated angioedema in rats. Genetic or environmental factors that decrease DPPIV activity might increase the risk of ACE inhibitor–associated angioedema.